1993
DOI: 10.1172/jci116371
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for fibrinogen Dusart (A alpha 554 Arg-->Cys) and its association with abnormal fibrin polymerization and thrombophilia.

Abstract: The molecular defect in the abnormal fibrinogen Dusart (Paris V) that is associated with thrombophilia was determined by sequence analysis of genomic DNA that had been amplified using the polymerase chain reaction. The propositus was heterozygous for a single base change (C -> T) in the Aa-chain gene, resulting in the amino acid substitution Aa 554 Arg Cys. Restriction analysis of the amplified DNA derived from the family members showed that his father and his two sons were also heterozygous. Electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
77
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(83 citation statements)
references
References 39 publications
1
77
1
1
Order By: Relevance
“…Finally, the mature clot is stabilized by covalent cross-linking of specific amino acids by a transglutaminase, factor XIIIa (1,2,13,14). The notion that αC regions are involved in fibrin formation is based on three clusters of data: (i) clot formation is slowed and the clot structure is perturbed when αC regions are removed from fibrinogen either proteolytically (15)(16)(17)(18)(19) or as a result of a natural/artificial genetic defect (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32); (ii) isolated αC fragments (19,33,34) or αC-specific antibodies (35,36) interfere with clot formation; (iii) αC regions polymerize and can be cross-linked by factor XIIIa, thus contributing to the clot stability (33,(37)(38)(39)(40).…”
mentioning
confidence: 99%
“…Finally, the mature clot is stabilized by covalent cross-linking of specific amino acids by a transglutaminase, factor XIIIa (1,2,13,14). The notion that αC regions are involved in fibrin formation is based on three clusters of data: (i) clot formation is slowed and the clot structure is perturbed when αC regions are removed from fibrinogen either proteolytically (15)(16)(17)(18)(19) or as a result of a natural/artificial genetic defect (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32); (ii) isolated αC fragments (19,33,34) or αC-specific antibodies (35,36) interfere with clot formation; (iii) αC regions polymerize and can be cross-linked by factor XIIIa, thus contributing to the clot stability (33,(37)(38)(39)(40).…”
mentioning
confidence: 99%
“…Electron microscopy of fibrinogen Caracas II (Aa 434 Ser → N-glycosylated Asn) has shown that the majority of its aC domains do not interact with the central E domain or with each other, and that the clots formed by this variant are more porous and less ordered than those of normal fibrin and have numerous free fibre ends (Maekawa et al, 1991;Woodhead et al, 1996). In fibrinogen Dusart extensive studies have shown that the point mutation Aa 554Arg → Cys results in abnormal lateral aggregation, causing thinner fibrin fibres with significantly decreased gel porosity and increased clot rigidity (Koopman et al, 1993;Siebenlist et al, 1993;Collet et al, 1993). It has also recently been shown that the mutation in fibrinogen Dusart introduces a tendency for the molecules to pre-assemble (Mosesson et al, 1996), and it has been suggested that this characteristic, together with the changes to clot architecture, are the main factors contributing to the high incidence of embolism found in affected individuals.…”
mentioning
confidence: 99%
“…Five independent families with AR554C-albumin binding have been identified and, strikingly, all propositi have presented with thrombosis [26]. Additionally, in vitro studies with the AR554C fibrinogen have demonstrated that impaired fibrinolysis, thinner and many branched fibers, increased clot stiffness, and an increased cross-linking potential probably explain the thrombosis and embolism seen in the families afflicted [22,[27][28][29][30]. It is interesting that for the BArg14Cys variants, which are the immediate vicinity of BGly15 residue and with a potential albumin binding (demonstrated in the propositus of Ijmuiden [12]; however, no others have been analyzed), severe thrombosis such as deep venous thrombosis, pulmonary embolism, or cerebral infarction has been reported in 6 out of the 8 families [4, [10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%